Frequency selective pitch transposition of audio signals - Disch, Sascha; Edler, Bernd (Proceedings of the IEEE 2011 Int. Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
Modern music production often uses pre-recorded pieces of audio, so-called samples, taken from a huge sample database. Consequently, there is an increasing demand to extensively adapt these samples to their intended new musical environment in a flexible way. Such an application, for instance, retroactively changes the key mode of audio recordings, e.g. from a major key to minor key by a frequency selective transposition of pitch. Recently, the modulation vocoder (MODVOC) has been proposed to handle this task. In this paper, two enhancements to the MODVOC are presented and the subjective quality of its application to selective pitch transposition is assessed. Moreover, the proposed scheme is compared with results obtained by applying a commercial computer program, which became newly available on the market. The proposed method is clearly preferred in terms of the perceptual quality aspect "melody and chords transposition", while the commercial program is favored by the majority with regard to the aspect "timbre preservation".<br